Body mass index, conversion rate and complications among patients undergoing robotic surgery for endometrial carcinoma. Issue 4 (December 2015) - Cunningham, Mary; Dorzin, Esther; Nguyen, Loan; Anderson, Elizabeth; Bunn, W.
Abstract A retrospective cohort study was performed to evaluate the relationship of BMI to conversion rate in patients undergoing robotic surgery for endometrial cancer. Secondary outcomes were operative times, number of lymph nodes retrieved, and complications. Women with endometrial cancer scheduled for robotic surgery from September 2008 to September 2012 were included. Women were divided into three groups based on BMI, and conversion rates to laparotomy were compared. Descriptive and comparative analyses were performed among non-obese, obese, and morbidly obese women who completed robotic surgery. 298 women were scheduled for robotic surgery for endometrial carcinoma: 87 non-obese (BMI 19–29, μ 25.23), 110 obese (BMI 30–39, μ 34.21), and 101 morbidly obese (BMI 40–71, μ 47.38). Conversion to laparotomy occurred in 18 patients (6%), with no difference in conversion rate between BMI categories. Direct comparison between converted and completed robotic patients showed no significant differences in preoperative characteristics, except that patients who required conversion had a higher number of previous abdominal surgeries. Patients completing robotic surgery underwent node dissections at similar rates in all three BMI categories. Operating room time, but not surgical time, was increased in morbidly obese patients. There were no significant differences in complications, performance of lymphadenectomy, or lymph node yields between BMI categories. Increase in BMI was not associated with an increase in rate of conversion to laparotomy or complication rate in patients undergoing robotic surgery for endometrial carcinoma. Node dissections were pathologically equivalent between BMI categories.